(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The problem of infectious diseases during antenatal fetal death with the discharge of amniotic fluid is one of the most pressing problems in obstetrics. Infection of the fetus in the womb during prenatal rupture of amniotic fluid can lead to complications during pregnancy, childbirth, or the development of diseases in the postpartum period.